2010
DOI: 10.3141/2172-10
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Staged Posttensioning to Abate Reflective Cracking on Side-by-Side Box-Beam Bridge Decks

Abstract: Side-by-side box-beam bridges are often used at sites with tight under-clearance requirements and specified for accelerated construction. However, longitudinal reflective deck cracking is a recurring problem for these bridges and it raises concern for their durability and long-term safety. North American practices of the transverse connection design of this particular bridge are discussed in NCHRP Synthesis 393, and the Michigan design is presented as the preferred procedure. The most recent design in Michigan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Since RDSK has been used as a direct indicator for shear key cracking [4,[7][8][9][12][13][14], it is crucial to accurately simulate the interface of the beam and shear key in finite element models (FEMs) using solid elements. Three commonly used methods are the full bond [15][16][17], friction [13,[18][19][20][21], and traction-separation model [13,[21][22][23]. Full bond is suitable for the interface of concrete and grout materials with strong bonding ability, such as epoxy, MgNH4PO4, and UHPC, but not for commonly used nonshrink grout and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Since RDSK has been used as a direct indicator for shear key cracking [4,[7][8][9][12][13][14], it is crucial to accurately simulate the interface of the beam and shear key in finite element models (FEMs) using solid elements. Three commonly used methods are the full bond [15][16][17], friction [13,[18][19][20][21], and traction-separation model [13,[21][22][23]. Full bond is suitable for the interface of concrete and grout materials with strong bonding ability, such as epoxy, MgNH4PO4, and UHPC, but not for commonly used nonshrink grout and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al ( 4 ) pointed out that radical changes in shear key geometry (i.e., very sharp corners) may result in higher stress levels. Ulku et al ( 5 ) found that the temperature gradient caused by weather changes is the main factor that causes cracks to develop near the top of shear key interfaces. Another cause of cracks was reported to be post-tensioning forces that are not uniformly distributed at the keyway because of shear lag.…”
mentioning
confidence: 99%
“…The bridge can be analyzed in its entirety: a plate with opposite edges simply supported and the other two edges free under uniformly distributed load; this is a macromechanical model of a precast orthotropic bridge (1,4). The formation process of the longitudinal cracks can be studied with the bonding relationships between cast-in-place and precast concrete (6,7,8,9,10).…”
mentioning
confidence: 99%
“…When the box beams are placed adjacent to each other, there is no continuity enabling them to function as a single structure. The small longitudinal joint between hollow core slabs, typically called a hinge joint, is normally filled with grout or an appropriate non-structural sealant to prevent water leakage and moisture penetration between beams, as well as to support load transfer ( 4 ). The deck is built with reinforced cast-in-place concrete.…”
mentioning
confidence: 99%
See 1 more Smart Citation